2019
DOI: 10.1101/520361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macroevolution of dimensionless life history metrics in tetrapods

Abstract: Life history traits represent organism's strategies to navigate the fitness trade-offs between survival and reproduction. Eric Charnov developed three dimensionless metrics to quantify fundamental life history trade-offs. Lifetime reproductive effort (LRE), relative reproductive lifespan (RRL), and relative offspring size (ROS), together with body mass, can be used classify life history strategies across the four major classes of tetrapods: amphibians, reptiles, mammals, and birds. First, we investigate how th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This raises interesting questions about the trait space of life-history parameters (e.g. Blonder et al 2014;Morrow et al 2019) and how they interact with dynamic environments to form communities (e.g. Enquist et al 2015;Enquist et al 2017;Burger et al 2019b).…”
Section: Trait Spacementioning
confidence: 99%
See 1 more Smart Citation
“…This raises interesting questions about the trait space of life-history parameters (e.g. Blonder et al 2014;Morrow et al 2019) and how they interact with dynamic environments to form communities (e.g. Enquist et al 2015;Enquist et al 2017;Burger et al 2019b).…”
Section: Trait Spacementioning
confidence: 99%
“…2014; Morrow et al . 2019) and how they interact with dynamic environments to form communities (e.g. Enquist et al .…”
Section: The Road Forward: Testing and Extending The Efpmentioning
confidence: 99%
“…These observations are consistent with that incubation time, larval period, and metamorphosis size (each of these traits contributes to the time that an organism spends to prepare to reproduce) turned out to be invariant toward body size in amphibians, but not in reptiles. Likewise, Morrow et al (2019) observed that lifetime reproductive effort and relative offspring size decrease with body mass in amphibians and squamates (although in squamates, this decrease is not significant for lifetime reproductive effort). Their two observations also strengthen our results.…”
Section: Ta B L Ementioning
confidence: 94%
“…Thus, adult life span divided by the time needed to reach maturity (time before reproduction vs. time available for reproduction) is on average smaller in amphibians than in reptiles (Morrow et al, 2019). It increases significantly with body mass in Squamata but is independent of body mass in amphibians (Morrow et al, 2019). These observations are consistent with that incubation time, larval period, and metamorphosis size (each of these traits contributes to the time that an organism spends to prepare to reproduce) turned out to be invariant toward body size in amphibians, but not in reptiles.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation